PENGETAHUAN DAN SIKAP REMAJA PUTRI TENTANG GANGGUAN MENSTRUASI DI KELAS XII SMAN 02 PEKANBARU - Zalni, Rummy Islami (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Menstrual disorders are more common in adolescents (16-19 years old), in the form of irregular menstruation, fewer menstruation and very much, menstrual pain and menstruation more often. The purpose of research to know the description of knowledge and attitude of young women about menstrual disorders in class XII SMAN 02 Pekanbaru. The research design is quantitative with descriptive method with cross sectional approach. The research was conducted on July 26 to August 16, 2013 at SMAN 02 Pekanbaru class VII in 2013. The population in this study is all students of class XII SMAN 02 Pekanbaru in 2013. Population in this research is all The students of grade XII SMAN 02 Pekanbaru in 2013 amounted to 149 people and the sample was taken by simple random sampling which was 60 people. Analysis of knowledge data used is univariate data analysis and attitude analysis using Likert scale. The result of the research shows that majority of respondents’ knowledge is 43 people (71.67%) and the majority of female attitudes about menstruation disorder in SMAN 02 Pekanbaru is negative 33 people (55%). It is expected that the results of this study can be used as information where menstrual disorders are important things to know. So that young women can overcome if the existence of menstrual disorders.